Effect of seasonal variation on the peak presentation of slipped capital femoral epiphysis. A comparison of children in Johannesburg, South Africa and London, UK. Issue 3 (May 2020) - Firth, Gregory B.; Foster, Matthew; Pieterse, Carl; Ramguthy, Yammesh; Izu, Alane; Bacarese-Hamilton, Joseph; Ramachandran, Manoj
Abstract : Variation exists in the peak presentation of slipped capital femoral epiphysis (SCFE). The objective of this study was to compare two cohorts of children (South Africa and the UK) and explore similarities and differences regarding demographic and epidemiological features, incidence and seasonal variation in peak presentation. Patients presenting with SCFE at one of two hospitals were included in the study. A retrospective cohort was collected from hospital records. The following factors were recorded: duration of symptoms, chronicity, stability, seasonality, severity and prophylactic pinning. A total of 137 patients were included in the study – 70 patients (80 hips) from South Africa and 67 patients (73 hips) from the UK. Both sites recorded more than 50% incidence of a chronic slip. There was higher delay to presentation in the UK compared with South Africa (90 vs 60 days, P = 0.0262). The UK population were more skeletally mature (32.8% open triradiate cartilage) compared with the South Africa population (64.9% open triradiate cartilage). In both populations, the most common season of symptom onset was summer. In the UK, the most common season of symptom presentation was in autumn compared with summer in South Africa. This study found significant differences in the two countries, including a more skeletally mature population in the UK. Both cohorts showed seasonal variation in peak incidence, but there was more seasonal variation in peak incidence in the UK – in the summer for onset of symptoms and autumn months for time of presentation.